Comparative study between the outcome of Laparoscopic Palomo and open inguinal Varicocelectomy (Journal of Dhaka Medical College, 2015)
Background: The ideal method of varicocele treatment is a controversial issue. The present study was designed to compare the outcome of laparoscopic palomo and open inguinal varicocelectomy. Methods: The present quasi experimental study was conducted in the Department of Urology, Dhaka Medical College Hospital, Dhaka, between July 2010 and June 2012 to compare the outcome of open inguinal and laparoscopic Palomo approach of varicocelectomy. Purposively selected 50 patients were divided into equal two groups, Group A and Group B treated with open inguinal varicocelectomy and laparoscopic Palomo varicocelectomy respectively. Statistical analyses were done by using SPSS and p value